2019
DOI: 10.1016/j.heliyon.2019.e02898
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of esterification routes for long chain cellulose esters

Abstract: Long chain cellulose esters are internally plasticized bio-based materials, which have good future potential in several applications such as coatings, films and plastics. The long chain cellulose esters with different side chain lengths were synthesized using different esterification methods. When homogeneous esterification was used, the acyl chloride method was the most effective esterification method and cellulose esters prepared using this method have the highest degree of substitution values (DS). In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 29 publications
0
24
1
Order By: Relevance
“…Even under acid conditions, the ratio of the catalyst and glucose monomer, reaction temperature, and reaction time affect the substitution rate of ester groups [29]. On the other hand, the hydrophobicity of starch increases as the length of the alkyl group substituted with the hydroxyl group of starch increases, but many experimental results have shown that the substitution rate is lowered by its steric hindrance [30]. These results mean that it is also necessary to consider the structure of the substituted alkyl carbonyl to synthesize the optimal biodegradable plastic according to the application.…”
Section: Esterification Of Starchmentioning
confidence: 99%
“…Even under acid conditions, the ratio of the catalyst and glucose monomer, reaction temperature, and reaction time affect the substitution rate of ester groups [29]. On the other hand, the hydrophobicity of starch increases as the length of the alkyl group substituted with the hydroxyl group of starch increases, but many experimental results have shown that the substitution rate is lowered by its steric hindrance [30]. These results mean that it is also necessary to consider the structure of the substituted alkyl carbonyl to synthesize the optimal biodegradable plastic according to the application.…”
Section: Esterification Of Starchmentioning
confidence: 99%
“…Esterified CNFs were prepared by liquid-phase reactions with carboxylic acid reagents or with acyl chloride reagents . CNF functionalization with carboxylic acids was performed by dispersing 200 mg of CNFs in 200 mL of deionized water followed by 2 h sonication before adjusting to approximately pH 4 with 4 M HCl.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Another potentially important factor to consider is that the extent to which the biodegradation of a functionalized nanomaterial is inhibited may be more closely linked to the degree of functionalization of the surface (DS surface ) than to DS overall . This distinction is important as the preliminary step in the biodegradation of a solid-phase material involves the adsorption and colonization of microorganisms at the surface. In the case of cellulosic materials, this initial biodegradation step requires biofilm formation or the interaction of highly specific microbe-secreted cellulosome complexes with their surface. , As nanocellulose fibers are composed of numerous cellulose chains woven together into a nanoscale cord, the chains at the fiber surface are distinct from those within the bulk of the material. ,, During chemical functionalization with liquid reagents, cellulose chains in both the bulk and the surface of nanocellulose are targeted, ,, while gas-phase reagents selectively functionalize the nanocellulose surface due to their inability to penetrate the bulk of the material. Despite the potential for achieving different levels of surface versus bulk functionalization, studies of cellulosic materials typically use only bulk-sensitive analytical techniques (e.g., NMR) and thus quantify only DS overall . ,, The effect of surface substitution is likely to be particularly important for the biodegradation of CNFs compared to macrocellulose due to the large surface area-to-volume ratio of nanocellulose as well as the decreased swelling capacity of CNFs, which limits access to bulk cellulose chains …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various methods have been introduced to make these cellulose esters. Cellulose is reacted with Fatty acid, acyl chloride, Fatty acid vinyl and fatty acid anhydride to produce a degree of substitution (DS), (DS number: 0.3 -1,3) depending on the fatty acid branch chain used [2]. OPEFB consists of 20.6-33.5% hemicellulose [3], 23.7-65.0% cellulose [4] and 14.1-30.5% lignin [5].…”
Section: Introductionmentioning
confidence: 99%